WHAT DRIVES TRANSFER PRICING PRACTICES? EVIDENCE FROM THE HEALTHCARE SECTOR - Karolina Kavnet Daeli; Mohamad Zulman Hakim; Audy Fiska Farah Diba; Naswa Zulfa Tuffahati; Septia Permatasari (PT. ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the influence of tenure audits, tax minimization, and debt covenants on transfer pricing practices in healthcare sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Transfer pricing is a pricing policy in transactions between parties that have a special relationship, which is often used by companies for tax efficiency purposes and financial performance management. This study uses a quantitative approach with a hypothesis testing method. The research population includes 38 healthcare sector companies on the IDX, while sample selection is carried out through purposive sampling with certain criteria until 13 eligible companies are obtained. The research data is in the form of secondary data sourced from the company's annual financial statements downloaded through the official IDX website (www.idx.co.id). The data analysis was carried out using linear regression of the panel data with the help of the EViews 12 software, as this model is able to accommodate data variations across time and between companies. The results of the study show that tenure audit and tax minimization do not have a significant effect on transfer pricing practices. This shows that the length of the auditor-client relationship and tax savings efforts do not necessarily affect transfer pricing decisions. In contrast, debt covenants have been shown to have a significant effect on transfer pricing practices, confirming that contractual pressures from debt agreements can motivate management to use transfer pricing. These findings are expected to make a theoretical and practical contribution to the development of accounting literature, regulators, investors, and corporate management.